Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.4 - Adding and Subtracting Rational Expressions with Different Denominators - Exercise Set: 28



Work Step by Step

$\frac{7x}{x-3}$-$\frac{4x+9}{x-3}$= $\frac{7x-(4x+9)}{x-3}$= $\frac{7x-4x-9}{x-3}$=$\frac{3x-9}{x-3}$=$\frac{3(x-3)}{x-3}$ = 3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.